Novel Nonreplicating Vaccinia Virus Vector Enhances Expression of Heterologous Genes and Suppresses Synthesis of Endogenous Viral Proteins - Linda S. Wyatt (American Society for Microbiology, 2017)
ABSTRACT Viruses are used as expression vectors for protein synthesis, immunology research, vaccines, and therapeutics. Advantages of poxvirus vectors include the accommodation of large amounts of heterologous DNA, the presence of a cytoplasmic site of transcription, and high expression levels. On the other hand, competition of approximately 200 viral genes with the target gene for expression and immune recognition may be disadvantageous. We describe a vaccinia virus (VACV) vector that uses an early promoter to express the bacteriophage T7 RNA polymerase; has the A23R intermediate transcription factor gene deleted, thereby restricting virus replication to complementing cells; and has a heterologous gene regulated by a T7 promoter. In noncomplementing cells, viral early gene expression and DNA replication occurred normally but synthesis of intermediate and late proteins was prevented. Nevertheless, the progeny viral DNA provided templates for abundant expression of heterologous genes regulated by a T7 promoter. Selective expression of the Escherichia coli lac repressor gene from an intermediate promoter reduced transcription of the heterologous gene specifically in complementing cells, where large amounts might adversely impact VACV replication. Expression of heterologous proteins mediated by the A23R deletion vector equaled that of a replicating VACV, was higher than that of a nonreplicating modified vaccinia virus Ankara (MVA) vector used for candidate vaccines in vitro and in vivo, and was similarly immunogenic in mice. Unlike the MVA vector, the A23R deletion vector still expresses numerous early genes that can restrict immunogenicity as demonstrated here by the failure of the prototype vector to induce interferon alpha. By deleting immunomodulatory genes, we anticipate further improvements in the system. IMPORTANCE Vaccines provide an efficient and effective way of preventing infectious diseases. Nevertheless, new and better vaccines are needed. Vaccinia virus, which was used successfully as a live vaccine to eradicate smallpox, has been further attenuated and adapted as a recombinant vector for immunization against other pathogens. However, since the initial description of this vector system, only incremental improvements largely related to safety have been implemented. Here we described novel modifications of the platform that increased expression of the heterologous target gene and decreased expression of endogenous vaccinia virus genes while providing safety by preventing replication of the candidate vaccine except in complementing cells used for vector propagation.